1996
DOI: 10.1007/bf01877970
|View full text |Cite
|
Sign up to set email alerts
|

A carlavirus-specific PCR primer and partial nucleotide sequence provides further evidence for the recognition of cowpea mild mottle virus as a whitefly-transmitted carlavirus

Abstract: Cowpea mild mottle virus (CMMV) has physicochemical properties typical of carlaviruses, but has remained unclassified due to a number of unusual properties, including no serological cross-reaction with l 8 carlaviruses; production of brush-like inclusion bodies in vivo; and the ability to be transmitted by whiteflies (Bermisia tabaci).In this paper we report the use of a carlavirus specific PCR primer to identify CMMV as a member of the carlavirus group. This is confirmed by nucleotide sequence (958 nucleotide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 15 publications
2
22
0
1
Order By: Relevance
“…The semi-flexuous-shaped particles observed in symptomatic yardlong bean plants suggested that the isolated virus was a carlavirus. Moreover, the host range, symptomatology induced in test plants, and transmission via seeds and by whiteflies, all agreed well with what has been reported for CPMMV [1,11,18,22], but the amplification of a ca. 0.9 bp fragment using carlavirus universal primers [13,21] was the most convincing argument for concluding that the virus isolated from yardlong bean is a carlavirus (Figure 3).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The semi-flexuous-shaped particles observed in symptomatic yardlong bean plants suggested that the isolated virus was a carlavirus. Moreover, the host range, symptomatology induced in test plants, and transmission via seeds and by whiteflies, all agreed well with what has been reported for CPMMV [1,11,18,22], but the amplification of a ca. 0.9 bp fragment using carlavirus universal primers [13,21] was the most convincing argument for concluding that the virus isolated from yardlong bean is a carlavirus (Figure 3).…”
Section: Resultssupporting
confidence: 87%
“…The virus was transmitted by whiteflies to these host species with an average efficiency of 56% and 52%, respectively. The symptoms induced following mechanical and insect transmission tests to host plants resembling those described for Cowpea mild mottle virus (CPMMV), a leguminous seed and whitefly-borne virus [11,18]. …”
Section: Resultsmentioning
confidence: 99%
“…Primers used in this work are described in Table 4. RT-PCR amplifications of cucumovirus, potyviruses, carlaviruses, luteovirures, SBMV and BnYDV, as well as PCR amplifications of TYLCV and geminiviruses, were conducted as previously described (Robertson et al 1991;Badge et al 1996;Wyatt and Brown 1996;Gibbs and Mackenzie 1997;Choi et al 1999;Accotto et al 2000;Verhoeven et al 2003;Segundo et al 2004a). Primers for detecting TSWV and PVuV were designed based on sequences retrieved from GenBank.…”
Section: Rt-pcr and Sequencingmentioning
confidence: 99%
“…It was concluded that NLV was neither a potyvirus nor a carlavirus but could be a member of a new genus with MacMV (Mowat et al, 1991). Moreover, a PCR primer designed to a sequence present in 80 % of all carlaviruses sequenced to date failed to produce a product with NLV or MacMV cDNA (Badge et al, 1996).…”
mentioning
confidence: 99%